Cover Image, Volume 12, Issue 1. (11th December 2019) - Mohsen, Mona O.; Speiser, Daniel E.; Knuth, Alexander; Bachmann, Martin F.
Abstract: The cover image is based on the Advanced Review Virus‐like particles for vaccination against cancer, by Mona O. Mohsen, Daniel E. Speiser, Alexander Knuth, Martin F. Bachmann. https://doi.org/10.1002/wnan.1579 . Abstract : The cover image is based on the Advanced Review Virus‐like particles for vaccination against cancer, by Mona O. Mohsen, Daniel E. Speiser, Alexander Knuth, Martin F. Bachmann. https://doi.org/10.1002/wnan.1579 .